Seções de choque diferenciais absolutas para o espalhamento elástico de elétrons de energias baixas e intermediárias por moléculas poliatômicas em fase gasosa - Homem, Manoel Gustavo Petrucelli (Universidade Federal de São Carlos, 2002)
In this work we report absolute elastic differential cross sections (DCS) measurements for electron collisions with OCS, CO2, CH4, NO, N2O, CHF3 e C2F6 molecules in gas phase. The measurements cover the angular range from 10o to 130o and energy range between 50-800 eV. Crossed electron beam-molecular beam geometry is applied to measure the relative intensity of the scattered electron as a function of the scattering angle. The scattered electrons are energy-filtered by a retarding-field energy selector. The recorded scattering intensities, as a function of the scattering angle, are converted into absolute elastic DCS s using the relative flow technique. Additionally, this work reports the development of a low energy electron scattering spectrometer (E<100 eV). In this spectrometer a new technique, a magnetic angle-changing device has been constructing to extend the measurements to backward angles (up to 180o). However, the application of this technique needs more systemization. Results of DCS s using the magnetic angle changer are reported only for the argon atom for the energy of 30 eV up to 120o, showing the future prospect of this technique. In the other hand, using the new spectrometer, DCS s data are reported for the CHF3 molecule for electron energies from 10 to 30 eV up to 85o scattering angle. In summary, several results of absolute differential cross sections for the elastic electron scattering are reported to several molecular targets. The comparison between our measured data and theoretical calculation using an optical potential to represent the electron-molecule interaction as well as other available experimental data in the literature shows good agreement. Our study has shown the significant role played by the absorption effects on the calculated cross sections in the intermediate energy range.
Keywords: Seções de choque; Espalhamento de elétrons; Espalhamento elástico de elétrons; Moléculas poliatômicas; CIENCIAS EXATAS E DA TERRA::FISICA